Coffee (Coffea arabica L,var. Castillo) seedling growth in Nariño, Colombia - Castillo, José Álvaro; Andrade, Danita (Revista de Ciencias Agrícolas, 2021)
Coffee is one of the most socioeconomically important crops worldwide. Currently, environmental variations due to climate change are affecting coffee development and growth. Therefore, it is important to evaluate areas that offer a different environment during seedling stage since it is fundamental for successful cultivation. Four municipalities located at different altitudes in the Department of Nariño were selected: La Florida (1879 m a.s.l.), Sandoná (1924 m a.s.l.), Consacá (2001 m a.s.l.), and La Unión (1417 m a.s.l.). The experiment was conducted as a randomized complete block design. Growth variables were measured for five months, including total height-TH, number of leaves-NL, total leaf area-LA, fresh weight-FW, and dry weight-W. The following indices were calculated from the variables recorded: relative growth rate-RGR, leaf area index-LAI, net assimilation rate-NAR, crop growth rate-CGR, leaf area duration-LAD, and leaf area ratio-LAR. The data related to TH, NL, W, and LA recorded during the last evaluation (120 days after being transplanted) showed differences between locations; the maximum values in TH, W and LA were recorded in La Union, while higher averages in NL were obtained in Sandoná. The index values for CGR, LAI, LAR, RGR, and LAD were higher in La Unión, while NAR was higher in La Florida. The results lead to conclude that there are differences in coffee seedling growth depending on the climatic conditions. Accordingly, the highest growth was observed in areas at lower altitudes; therefore, these are recommended for seedling establishment given the higher growth rate, especially that of leaves.